2014
DOI: 10.1155/2014/563981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prevalence of Synovitis by Ultrasound Assessment in Subjects Exposed or Not to Self-Reported Physical Overexertion: The Monday’s Synovitis

Abstract: Objective. To compare the proportion of synovitis detected by ultrasonographic study (USS) of the hands, in subjects with no rheumatologic known disease according to self-reported level of overexertion performed the day before. Methods. 407 consecutive volunteers were enrolled in a twelve-month period and underwent an ultrasound assessment of the hand. All studies were performed on Monday or Friday. Subjects were grouped according to their self-reported overexertion carried out the day before. Presence or abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…15 On the other hand, we have considered the prevalence of synovitis in healthy subjects recently described (11.5–12.1%). 23 For a 95% confidence level, an accuracy of 5% and assuming a similar scenario that was found by Yoon et al., the sample size calculated was 76 individuals. Assuming the pessimistic scenario based on the results of Demirkaya et al., the sample size would be 90.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…15 On the other hand, we have considered the prevalence of synovitis in healthy subjects recently described (11.5–12.1%). 23 For a 95% confidence level, an accuracy of 5% and assuming a similar scenario that was found by Yoon et al., the sample size calculated was 76 individuals. Assuming the pessimistic scenario based on the results of Demirkaya et al., the sample size would be 90.…”
Section: Methodsmentioning
confidence: 85%
“…In this regard, previous studies have suggested that grade I synovitis should not necessarily be considered pathological since it can be identified in healthy subjects or induced after physical activity and disappear after rest. 23,32 Reporting synovitis prevalence studies using composite indices is probably most appropriate for comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Grenzen des Normalen zum Pathologischen sind nicht nur fließend sondern zudem von äußeren Einflußfaktoren abhängig. In einer Studie wurden signifikant häufiger synoviale Hypertrophie, Erguss und/oder Power-Doppler-Aktivität bei Patienten gefunden, die sich am Tag vor der Untersuchung körperlich überanstrengt hatten im Vergleich zu Patienten, die diese Anstrengung nicht angaben, weshalb dazu geraten wird eine US-Untersuchung so viele Tage wie möglich nach einer solchen Anstrengung durchzuführen [10].…”
Section: Sonografischer Und Dopplersonografischer Befund Am Gelenk Ununclassified
“…Several previous studies have addressed the effect of handedness on RA progression. Most of them compared both hands in terms of radiological score, hand deformity, handgrip strength and Ritchie articular index (RAI) (3)(4)(5). These studies concluded that hand dominance has an impact on the disease course, and hypothesized that mechanical stress increase the disease plateau (3,4), which is mainly seen in early RA (5,6).…”
mentioning
confidence: 99%